Partial maxillary osteotomy following an unsuccessful forced eruption of an impacted maxillary canine: 10 year follow-up. Review and case report (Journal of Applied Oral Science, 2012)
The maxillary canines are amongst the most frequently impacted teeth, second only to the third molars. Several conservative orthodontic and surgical techniques are available to position the teeth properly in the dental arch, even in severe cases. However, when an extraction is necessary, it often leaves a critical alveolar defect of difficult management. The authors present the technique of Partial Maxillary Osteotomy, in which a dento-alveolar segment is moved mesially, hence closing the remaining space, allowing for the formation of healthy periodontium and resulting in an adequate functional and aesthetic outcome. A case report is presented with a 10 year follow-up, proving the technique's stability in the long term.